A Double Auction Mechanism for Heterogeneous Multi‐unit Spectrum Trading. Issue 5 (1st September 2016) - Sun, Yu'e; Li, Meixuan; Huang, He; Tian, Miaomiao; Li, Fanzhang; Huang, Liusheng
Abstract : The last decade has witnessed a rapid growth in wireless communications technology, and as a result the demand for spectrum resources increased rapidly. Unfortunately, many new wireless demanders cannot access the limited wireless licenses in time while large chunks of spectrum are idle. To solve this, we design a multiunit double auction mechanism for heterogeneous spectrum channels, which take the spatial and temporal reuse into consideration. The proposed scheme first introduces the multi‐participants multi‐heterogeneous‐spectrum trading double auction to illustrate the system model. Some techniques such as spectrum categorize, virtual sellers and buyers' conflict graph construction, and reconstruction of buyer groups are adopted to achieve a high efficiency of the algorithm. Then, we also prove the truthfulness, individual rationality, and budget balance of the proposed scheme. Finally, the simulation results show that the practical performance of the proposed scheme can efficiently improve the spectrum transaction ratio, reuse ratio, and the buyer's satisfactory ratio.